Iterative Rupture of the Patellar Tendon: A Case Report of an Original Technique for Revision Reconstruction Using an Adjustable Loop and an Artificial Ligament - N. Bouguennec; P. Colombet (Case Reports in Orthopedics)
Chronic rupture of the patellar tendon is a severe injury that leads to dramatic functional consequences including lack of extension and walking difficulty. Surgery is the gold standard to treat this type of injury, but revision reconstructions are problematic because an ipsilateral graft was often harvested for the initial surgery. Because fibrotic tissues on the patellar tendon need to be debrided, another graft must be added to reinforce the tendon. We reported the case of a former semiprofessional handball player, a 29-year-old man who presented an iterative rupture with the fracture of the transverse patellar tunnel 6 months after reconstruction using a semitendinosus graft and suture repair. We performed revision reconstruction surgery using an artificial ligament placed between the extensor mechanism and the tibia for extra-articular reinforcement to maintain extensor mechanism continuity. Two adjustable loops were also used to repair the patellar tendon tear. At 2-year follow-up, the patient was able to resume the practice of handball at a competitive level with good clinical and functional results. This technique can therefore be used as a salvage procedure for chronic iterative rupture of the patellar tendon.